2017
DOI: 10.1063/1.4990612
|View full text |Cite
|
Sign up to set email alerts
|

The quantum structure of anionic hydrogen clusters

Abstract: A flexible and polarizable interatomic potential has been developed to model hydrogen clusters interacting with one hydrogen anion, (H)H, in a broad range of sizes n = 1-54 and parametrized against coupled cluster quantum chemical calculations. Using path-integral molecular dynamics simulations at 1 K initiated from the putative classical global minima, the equilibrium structures are found to generally rely on icosahedral shells with the hydrogen molecules pointing toward the anion, producing geometric magic n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 49 publications
(64 reference statements)
1
12
0
Order By: Relevance
“…Our goal is to investigate whether well-defined and compact shells are formed and what their structure is. In addition, since the H 2 -Cs + interaction is very anisotropic, we believe that it is worth studying the H 2 /D 2 orientational effects 10,31,32 by explicitly taking into account their rotational degrees of freedom and comparing with the more widely used pseudoatom model. The importance of three-body (3B) induction forces [33][34][35][36] is assessed as well.…”
Section: Introductionmentioning
confidence: 99%
“…Our goal is to investigate whether well-defined and compact shells are formed and what their structure is. In addition, since the H 2 -Cs + interaction is very anisotropic, we believe that it is worth studying the H 2 /D 2 orientational effects 10,31,32 by explicitly taking into account their rotational degrees of freedom and comparing with the more widely used pseudoatom model. The importance of three-body (3B) induction forces [33][34][35][36] is assessed as well.…”
Section: Introductionmentioning
confidence: 99%
“…We have not attempted to quantify the mutual couplings just described, but there is a growing literature on ab initio structural models of molecular hydrogen nanoclusters, and such models could be used to assess the electrical environments in which the H 2 moieties reside. For nanoclusters of the type H H n 2 -( ) , structures have been determined using a variety of quantum chemical methods (e.g., Huang et al 2011;Calvo & Yurtsever 2018;Mohammadi et al 2020). We note that Calvo & Yurtsever (2018) obtained results in accord with the mass spectroscopy of anion clusters undertaken by Renzler et al (2016), who demonstrated the existence of "magic numbers" n = 12, n = 32, and n = 44, consistent with icosahedral solvation shells.…”
Section: Nanoclustersmentioning
confidence: 54%
“…For nanoclusters of the type H H n 2 -( ) , structures have been determined using a variety of quantum chemical methods (e.g., Huang et al 2011;Calvo & Yurtsever 2018;Mohammadi et al 2020). We note that Calvo & Yurtsever (2018) obtained results in accord with the mass spectroscopy of anion clusters undertaken by Renzler et al (2016), who demonstrated the existence of "magic numbers" n = 12, n = 32, and n = 44, consistent with icosahedral solvation shells.…”
Section: Nanoclustersmentioning
confidence: 54%
“…For nanoclusters of the type H − (H 2 ) n structures have been determined using a variety of quantum chemical methods (e.g. Huang et al 2011;Calvo & Yurtsever 2018;Mohammadi et al 2020). We note that Calvo & Yurtsever (2018) obtained results in accord with the mass spectroscopy of anion clusters undertaken by Renzler et al (2016), who demonstrated the existence of "magic numbers" n = 12, n = 32 and n = 44, consistent with icosahedral solvation shells.…”
Section: Nanoclustersmentioning
confidence: 76%